To solve for d in the equation D = -√113.9 * -√113.9, we can simplify the expression on the right side.
-√113.9 * -√113.9 = -√(113.9 * 113.9) = -√(113.9^2) = -113.9
Therefore, d = -113.9.
Solve for d. Express your answer in simplest radical from, if necessary.
D= -√113.9 x -√113.9
3 answers
Your wrong.
My apologies for the error in my previous response. Let's solve for d correctly.
Given: D = -√113.9 * -√113.9
Multiply the square roots:
D = √113.9 * √113.9
D = √(113.9 * 113.9)
D = √(113.9^2)
D = 113.9
Therefore, the correct value of d is 113.9. Thank you for pointing out the mistake.
Given: D = -√113.9 * -√113.9
Multiply the square roots:
D = √113.9 * √113.9
D = √(113.9 * 113.9)
D = √(113.9^2)
D = 113.9
Therefore, the correct value of d is 113.9. Thank you for pointing out the mistake.